2021
DOI: 10.1007/s00330-021-07809-w
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-iodine-dose dual-energy coronary CT angiography: qualitative and quantitative comparison between virtual monochromatic and polychromatic CT images

Abstract: Objectives To quantitatively evaluate the impact of virtual monochromatic images (VMI) on reduced-iodine-dose dual-energy coronary computed tomography angiography (CCTA) in terms of coronary lumen segmentation in vitro, and secondly to assess the image quality in vivo, compared with conventional CT obtained with regular iodine dose. Materials and methods A phantom simulating regular and reduced iodine injection was used to determine the accuracy and precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
2
20
0
2
Order By: Relevance
“…The examinations have been performed on a dual-layer dual-energy CT (iQon; Phillips, Haifa, Israel) consisting of a first pass arterial phase and late phase 10 min after injection. Acquisition parameters were a retrospective gated ECG acquisition at 120 kVp, with a cardiac care mas dose modulation (full dose 78%, half dose 40%), a pitch value at 0.20, and a rotation time at 0.27 s. Further technical details are provided in previous studies [ 17 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The examinations have been performed on a dual-layer dual-energy CT (iQon; Phillips, Haifa, Israel) consisting of a first pass arterial phase and late phase 10 min after injection. Acquisition parameters were a retrospective gated ECG acquisition at 120 kVp, with a cardiac care mas dose modulation (full dose 78%, half dose 40%), a pitch value at 0.20, and a rotation time at 0.27 s. Further technical details are provided in previous studies [ 17 , 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, both proposed protocols can be employed in clinical practice for both myocardial and coronary assessment. Indeed, a study carried out on the same population demonstrated the non-inferiority of the low rate injection protocol for coronary artery assessment (18). Nevertheless, the injection protocol with higher rate might provide more accurate calculations of iodine concentrations as different studies have shown an increase in accuracy for higher iodine concentrations (15,17).…”
Section: Discussionmentioning
confidence: 99%
“…retrospectively included. The entirety of this population has been the object of coronary artery image quality assessment (18). All subjects underwent a preliminary non-contrast acquisition to calculate the calcium score and only those with an Agatson score <400 were further evaluated (N=207).…”
Section: Methodsmentioning
confidence: 99%
“…We used a custom-made (Lausanne University Hospital, Lausanne, Switzerland) 10-cm-diameter cylindrical module made of low-density polyethylene (PE, average CT number at 100 kVp ≈ −100 HU). This module had a 5-cm-diameter central hole that was filled with an iodinated contrast material (CM) solution (Iomeprol 400 mixed with normal saline; Iomeron 400 ® , Bracco Imaging France, Massy, France) at a concentration of 18 mg I/mL, yielding CT numbers in the range of clinical CCTA at 100 kVp (approximately 350 HU) [ 4 ]. This CM solution and the surrounding PE created a pair of materials approaching the object-to-background contrast difference (|ΔHU|) encountered in CCTA, assuming that coronary arteries are opacified by iodinated CM and are surrounded by epicardial fat whose CT number is around −100 HU.…”
Section: Methodsmentioning
confidence: 99%
“…DECT is becoming widely available clinically and can now be used to improve patient safety and diagnostic performance in everyday practice. In cardiovascular medicine, in particular, DECT helps reduce iodine dose [ 3 , 4 ], improve vessel opacification [ 5 ], save radiation dose with virtual non-contrast reconstruction [ 6 ], among others. On the other hand, DECT suffers from some fundamental limitations, including the absence of notable improvement in spatial resolution or electronic noise compared with single-energy systems, which could be addressed by photon-counting-detector (PCD) technology [ 7 ].…”
Section: Introductionmentioning
confidence: 99%